Pulmonary function test in OSMF patients - Rashmi Nivsarkar; Abhijeet Deoghare; Anukriti Vishwakarma; Pooja Salkar (Wolters Kluwer Medknow Publications, 2020)
Betel nut quid chewing is a common psychoactive substance or masticatory euphoriant used by 600 million people in the world and is a main etiological factor for Oral Submucous Fibrosis (OSMF). The areca nut metabolite arecoline causes aggravation of disease in asthmatics by increasing bronchoconstriction in a dose-dependent manner; however, the effect of betel (Areca catechu) nut chewing on the function of the normal human lungs is yet to be fully established. Aim: The aim of the study was to measure and to compare pulmonary function tests such as forced vital capacity (FVC), forced expiratory volume (FEV), FEV/FVC%, peak expiratory flow rate, and maximum voluntary capacity maximum voluntary capacity (MVV) between study groups (control and OSMF). Materials and Methods: The study population included 100 participants comprising 50 normal and 50 clinically diagnosed OSMF cases. Pulmonary function tests were assessed using spirometer. Data were statistically analyzed. Results: Pulmonary function tests were found to be decreased in OSMF patients when compared to controls. Conclusion: There were no statistically significant differences (P > 0.05) in the spirometry parameters between both the groups; however, a decrease in pulmonary function compared to normal can be a warning sign for obstructive and restrictive type of pulmonary disease.